Knight's Tales: Looking at Representations of the Knight on Film - Martins, Ana Rita, 1970- (2014)
The knight dominated the medieval world and distinguished it from the classical era. However, in the early Middle Ages the knight was little more than a mounted warrior whose strength and prowess in battle could be procured by the wealthiest lord. In fact, it was only in the 11th century that these men started acquiring a specific status and only later did knighthood and chivalry become tied. Today, the knight remains a leading figure and is at the center of many modern adaptations of the medieval period. The present paper will focus on different portrayals of the knight in English-speaking films. What medieval features are kept? To what extent is accuracy important? How do these films contribute to our own modern day view of the knight and the Middle Ages? These are some of the questions this short paper seeks to answer.